THU0361 Paraneoplastic arthritis: A multi-centered experience. (23rd January 2014) - Kisacik, B.; Onat, A.M.; Kasifoglu, T.; Pehlivan, Y.; Pamuk, O.N.; Dalkilic, E.; Dönmez, S.; Bilge, S.Y.; Yilmaz, S.; Erdem, H.; Mercan, R.; Ozturk, M.A.; et al.
Abstract : Background: Paraneoplastic syndromes may mimic many symptoms like rheumatologic disease manifestations, hematologic disease, and vascular disease. Objectives: Paraneoplastic syndromes are defined by clinical, radiological or laboratory findings associated with malignant disease, but without a direct invasion of malign cells. Paraneoplastic syndromes precede cancer by no longer than two years. Musculoskeletal symptoms of paraneoplastic syndromes can be varied and difficult to differentiate. We attempt to report the laboratory and clinical findings of 55 patients admitted to different rheumatology clinics with rheumatic symptoms who were diagnosed with paraneoplastic arthritis. Methods: Thirteen rheumatology centers participated in the study. The study population consist of 55 patients (male/female: 38/17) and 35 patients with rheumatoid arthritis (RA) patients as the control group (male/female: 21/14). Paraneoplastic group was divided into two sub-groups as hematologic malignancies and solid tumors. Results: Mean age of patients with paraneoplastic arthritis and controls with RA control subjects were 48.7±16.2 and 51.9±12.1 respectively. The mean ages and gender distribution of the groups' were similar. The mean age of the patients in solid tumor group were significantly higher than the hematological malignancy group (53.2±12.7 vs 43.2±15.5 p= 0.001).When the clinical features and laboratory findings of RA group was compared with paraneoplastic arthritis, symmetric poly-arthritis, rheumatoid factor and anti cyclic cyctrullinated peptide (anti-CCP) presence were favorably higher among RA patients. Conclusions: In our cohort, leukemia, lymphoma and lung cancers were the leading diseases emerged as the final diagnosis of paraneoplastic arthritis. Rheumatoid arthritis patients were differentiated from paraneoplastic arthritis with high symmetric joint involvement, higher rheumatoid factor and anti-CCP positivity. Disclosure of Interest: None Declared